Keselarasan Strategis antara Green Marketing dan Tanggung Jawab Lingkungan dalam Mewujudkan Perdagangan Berkelanjutan - Muhammad Ichsan (CV. ITTC INDONESIA, 2025)
In the era of climate change and rising consumer awareness, sustainable trade practices have become a strategic necessity for businesses. This study aims to explore and synthesize recent literature (2021–2025) on the strategic alignment between marketing functions and environmental responsibility within the context of sustainable trade. A systematic literature review (SLR) was employed using a qualitative-descriptive approach. The findings reveal that green marketing strategies, including eco-friendly product innovation, sustainable distribution, and transparent communication, positively contribute to consumer loyalty, brand awareness, and corporate reputation. However, emerging challenges such as greenwashing and greenhushing threaten the credibility and effectiveness of these initiatives. This study underscores that the success of sustainable trade practices depends on strong integration between marketing strategies and environmental policies, supported by innovation, transparency, and robust regulation. The findings offer valuable insights for policymakers and business practitioners in designing ethical, adaptive, and sustainable trade strategies.